Intralesional curettage versus prosthetic replacement for bone tumors — a finite element analysis case of limb salvage simulation in biomechanics. (January 2021) - Peng, Matthew JianQiao; Cao, XiongWei; Chen, Hai-Yan; Hu, Yong; Li, XinXu; Lao, YongQiang; Bai, Bo
Highlights: Curettage or Prosthetics for GCT controversial. Surgical simulation adjusting limb salvage surgery. Numerical models harmless to humans. Stress & displacement analyzed by FEA. Prosthetic replacement is optimal. Abstract: Background and objectives: To compare mechanical properties of femoral tumor treatments so that better operative strategy for limb tumors surgery is optimized. Methods: Fourteen femoral CT images were randomly selected to rebuild 3D models by MIMICS. They were then executed by reverse engineering softwares for simulative modes. Mode #1: Intralesional curettage with cement filled plus fixator; Mode #2: Distal femur resection with tumorous prosthesis replaced. Finally, the mechanical aspects such as stress and displacement were compared by finite element analysis. Results: Analyzed by AnSys, the observation indexes were measured as follows: for displacement of femurs, d=1.4762 (< a=3.9042 < c=3.9845 < b=4.1159) in mm is the most staple of all models; for displacement of implants (fixators or prostheses), it's similar to the behavior of femurs and with no significant difference; for stresses of femurs, no significant difference was found among all models; the stresses of implants (fixations and prostheses) were observed as d=39.6334 (< a=58.6206 < c=61.8150 < b=62.6626) in MPa correspondently, which is the least; for stresses of the general system, the average of peak values for integrated devices of all models are: d=40.8072 (< a=58.6206 < c=61.7831< b=62.6626) in MPa, which is also the least. As a final result, both maximum values for displacement and stress of mode 2 are lower than those of mode 1. Conclusions: Our finite element analysis of limb salvage simulation in biomechanics proved that, to treat distal femoral bone tumors, prosthetic replacement is more efficient than intralesional curettage. Graphical abstract: Image, graphical abstract